Progressive lesions of central nervous system in microcephalic fetuses with suspected congenital Zika virus syndrome. (8th November 2017) - Sarno, M.; Aquino, M.; Pimentel, K.; Cabral, R.; Costa, G.; Bastos, F.; Brites, C.
ABSTRACT: Objective: To describe the pattern and progression of central nervous system (CNS) lesions in microcephalic fetuses with suspected Zika virus (ZIKV) infection. Methods: In this prospective study in Salvador, Brazil, we analyzed fetuses diagnosed with microcephaly and suspected ZIKV infection after a routine primary care ultrasound scan between July 2015 and February 2016 raised suspicion of fetal microcephaly. The pregnancies were followed with serial ultrasound scans until delivery at one of the three main referral centers for fetal abnormalities in Salvador, Brazil. Microcephaly was diagnosed when the head circumference was two or more SDs below the mean for gestational age and its relationship with ZIKV infection was defined according to the World Health Organization's criteria. All women were interviewed, to assess potential factors associated with fetal microcephaly. Serology test results for toxoplasmosis, cytomegalovirus, rubella, syphilis and human immunodeficiency virus (HIV) were recorded, as were previous routine ultrasound results. Signs/symptoms of infection during the pregnancy were noted. Results: Of 60 cases of suspected ZIKV‐related fetal microcephaly seen during the study period, eight were excluded due to serological evidence of other congenital infections or major ultrasound chromosomal markers. In the remaining 52 fetuses, microcephaly was diagnosed between 19 and 40 (median, 27.7; interquartile range, 23.4–32.0) weeks of gestation. The main ultrasound findings were: ventriculomegaly (65.4% of cases), cerebral calcifications (44.2%) and posterior fossa abnormalities (32.7%). 9.6% presented with arthrogryposis as an associated finding. Microcephaly was an isolated finding in four cases (7.7%). While ventriculomegaly was progressive in 41.2% of cases with this finding, the velocity of head circumference increase decreased progressively in almost all cases. Exanthematic disease was present in the majority (86.5%) of the women, 67.3% presenting in the first trimester of pregnancy. Additional lesions were detected after birth in 71.4% of the 35 cases with neonatal follow‐up. Conclusions: The majority of cases of congenital ZIKV syndrome have other ultrasonographic findings in addition to microcephaly. ZIKV‐related CNS anomalies present mainly as progressive CNS lesions and slowing rate of growth of the fetal head, and this seems to be evident only in the late second trimester, even when maternal infection occurs in the first trimester. Other ultrasound findings, such as ventriculomegaly, brain calcifications and posterior fossa destruction lesions, are also common in this congenital syndrome. Posterior fossa destruction lesions and arthrogryposis are an uncommon finding in other congenital infections, perhaps suggesting a novel severe congenital syndrome associated with fetal ZIKV. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.